Effects of network connectivity on viscoelastic relaxation in transient networks using experimental approach - Katashima, Takuya; Kudo, Ryota; Onishi, Ryoya; Naito, Mitsuru; Nagatoishi, Satoru; Miyata, Kanjiro; Tsumoto, Kouhei; Chung, Ung-Il; Sakai, Takamasa (Frontiers in Soft Matter, 2022)
The effect of network connectivity on viscoelastic relaxation in transient networks with well-defined structures (Tetra-PEG slime) was experimentally evaluated and compared to bond dissociation kinetics. To control the connectivity and discuss the pure effect precisely, we mixed the precursors in off-stoichiometric ratio. With decreasing network connectivity, the viscoelastic relaxation time accelerated and became shorter than the bond dissociation time. With increasing polymer concentration, the connectivity at which the viscoelastic relaxation time matched the dissociation time shifted to the high-connectivity region. The dependence of viscoelastic relaxation on connectivity can be adequately explained within the framework of the lifetime of a backbone. The backbone has numerous breakage points in low-connectivity region nearby the gelation point, resulting in a shorter lifetime than the dissociation time. However, the Rubinstein-Semenov model based on backbone relaxation does not predict the concentration dependence, suggesting that the formation of the network in the dilute/semi-dilute region deviates from a random branching process. These findings provide a crucial foundation for the molecular comprehension of transient network materials.